2015
DOI: 10.1155/2015/470801
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrical Discharge Machining: A Suitable Process for Machining Ceramics

Abstract: Today ceramics are used in many industrial applications, for example, in the biomedical field, for high-temperature components or for cutting tools. This is attributed to their excellent mechanical and physical properties, as low density, high strength, and hardness or chemical resistance. However, these specific mechanical properties lead to problems regarding the postprocessing of ceramics. In particular, cutting processes require expensive tools which cause high manufacturing costs to machine ceramics. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The amount of material removed is very small, and is flushed away with the continuously flowing fluid. The downward movement of the tool will produce the desired shape on the workpiece [7] [13]. Many attempts have been made by the researches to find the suitable method of machining.…”
Section: Principle Of Edmmentioning
confidence: 99%
“…The amount of material removed is very small, and is flushed away with the continuously flowing fluid. The downward movement of the tool will produce the desired shape on the workpiece [7] [13]. Many attempts have been made by the researches to find the suitable method of machining.…”
Section: Principle Of Edmmentioning
confidence: 99%
“…Figure 5 shows the classification of ceramics based on their conductivity values. The minimum electrical conductivity required for electrical discharge machining is about 10 −2 /Ωcm [55]. All metallic materials fulfil this demand.…”
Section: Ceramic Materialsmentioning
confidence: 99%
“…This allows the machining of geometrical features with diameter of less than 5 µm and a depth of less than 1 µm. In such conditions, the achievable surface roughness is lower than 1 µm [55]. The precision and accuracy of the final products are much higher in micro-EDM [76].…”
Section: Principle Of Edmmentioning
confidence: 99%
“…After finishing the AE, a layer of pyrolytic carbon (PyC) is deposited on the workpiece surface disassociating the carbonic dielectric in absence of oxygen and at a temperature of 1000-20000C. In experimental investigations it is observed that during the R-C pulse micro-EDM of nonconductive ceramics, pulse-off time is longer than that in conductive materials and effect of alternating thermal stress resulting spalling in addition to melting and evaporation [Chen et al, 2010;Sabur et al, 2013;Schubert et al, 2011;Schubert et al, 2015]. Sometimes, spalling becomes dominant over other removal mechanisms.…”
Section: Introductionmentioning
confidence: 99%